Komunikasi Mitigasi Bencana di Kota Industri Cilegon - Yunia, Anita; Yulianti, Wulan; Harwinda, Alfilonia; Pinariya, Janette Maria (Institut Komunikasi dan Bisnis LSPR, 2023)
Indonesia's geographical and geological factors, which are located on the Pacific Ring of Fire, are one of the factors causing earthquakes, volcanic eruptions, tsunamis, floods, landslides, and extreme weather. One area that is of concern to the government in its disaster management efforts is Cilegon City, Banten Province because it has a fairly high level of disaster vulnerability. This city has the potential for a large earthquake accompanied by a tsunami with waves as high as 8.28 meters which holds the potential for danger in the form of technological failures that cause damage to infrastructure, disease, the environment, and even death to humans. This research aims to analyze program steps and mitigation communication strategies in the city of Cilegon. This research was conducted in January – September 2022 in Cilegon City, Banten Province. The method used in this research is descriptive qualitative. The results show that efforts focused on dealing with disasters in Cilegon City were carried out through outreach and education. As a follow-up to this activity, the community will be empowered with training and assistance which will later be further developed with capacity-building activities to improve community skills in disaster response.